PENINGKATAN KUALITAS TIDUR PADA IBU RUMAH TANGGA DENGAN SENAM AEROBIK - Oktaviana, Elisa; Nadrati, Bahjatun; Dedy Supriatna, Lalu; Zulhendry, Zulhendry (Jurnal LENTERA, 2024)
Sleep quality is a description that explains a person's ability to maintain sleep time and the absence of disturbances experienced during the sleep period. Sleep quality is an illustration of how a person can easily start sleeping and maintain sleep. The quality of a person's sleep can be seen from the aspect of the length of time they sleep, and the complaints they feel during sleep or after waking up. There are 431 housewives in Kekeri hamlet. This community service was carried out in May 2023 by first providing an explanation to housewives in East Kekeri hamlet of the benefits of aerobic exercise to improve sleep quality using the lecture method then continuing on the following day, namely implementing aerobic exercise every afternoon for housewives There were 18 people present. Participants were then given a questionnaire about sleep quality before and after doing aerobic exercise 3 times a week for 1 month with a total of 12 meetings. The results of community service activities that have been carried out in East Kekeri Hamlet show that there is a difference in the average quality of sleep before and after aerobic exercise where the quality of sleep has increased. Aerobic exercise has the effect of improving the quality of sleep in housewives, this is very useful so that people know how to treat insomnia independently in an easy way.